Biomedical Potentialities of Silver Nanoparticles for Clinical Multiple Drug-Resistant Acinetobacter baumannii. (4th February 2019) - Chen, Minghui; Yu, Xiaoxu; Huo, Qianyu; Yuan, Qin; Li, Xue; Xu, Chen; Bao, Huijing
Abstract : Multidrug-resistant A. baumannii is increasingly recognized as a significant problem in hospitals and causes high morbidity and mortality. Here, we studied the antibacterial effects of AgNPs on clinically isolated multiple drug-resistant A. baumannii, and search for the potential antibacterial mechanism. Based on the results from the colony-forming unit (CFU) method, flow cytometry (FC), and a BrdU ELISA, we conclude that AgNPs can simultaneously induce apoptosis and inhibit new DNA synthesis in bacteria in a concentration-dependent manner. This study presents the first discussion of an antibacterial effect by AgNPs in clinically isolated, multidrug-resistant A. Baumannii and provides a new strategy for the use of silver nanoparticles in the multidrug-resistant A. Baumannii clinical problem.